Artificial Feeding in the Delivery of Specialized Medical Care to Patents (a Lecture) - D. G. Dantsiger (Общая реаниматология)
The grave condition of patients in intensive care units is largely due to improper nutritive support. Current views on proper artificial feeding are based on the awareness of principles of the balance of nutrients, a predominant role of enteral over parenteral feeding, which can be rightfully considered to be an innovation technology in medicine.